On the Movement of Granular Materials in Bins and Hoppers Part I: Two-Dimensional Problems - Szczepiński, W. (Engineering Transactions, 2003)
The paper is devoted to commemoration of the contribution of Professor Jerzy Litwiniszyn to the development of the mechanics of granular media A simple numerical procedure for determining the field of displacements of granular media in bins and hoppers is proposed. The procedure is based on the concept of Jerzy Litwiniszyn, who treated the gravity flow of granular media as a stochastic process. He and his co-workers presented analytical solutions to a certain number of simple problems concerning deformations of terrain caused by underground mining operations. The numerical procedure proposed in this paper is much more effective in solving numerous problems of practical significance.